An investigation of droplet flow in micro-channels - Tay, Yoke Gee. (2010)
The aim of this research report is to study and understand the characteristic of the droplet generated downstream of a formation junction. In microfluidics, there are many approaches toform droplet. Two such methods is the usage of a T-junction of a Y-junction. For this research, the droplet length, droplet distance and droplet generation time for both type of junction are